Macrophages infiltration and oral potentially malignant disorders: A systematic review and meta-analysis - Lara Krusser Feltraco; Julia Rodrigues Fernandes; Leonardo Francisco Diel; Leonardo da Silva Bittencourt; Lisiane Bernardi; Marcelo Lazzaron Lamers (Oral Oncology Reports)
Objective: Oral potentially malignant disorders often show a chronic inflammatory profile resulting in cellular changes at epithelial and stromal components. Since oral squamous cell carcinoma shows an association between macrophages and a worse prognosis, we hypothesize that macrophages could also be involved in the evolution of oral potentially malignant disorders into oral squamous cell carcinoma. Herein, we conducted a systematic review with meta-analysis in order to assess the role of macrophages in oral potentially malignant disorders severity and prognosis. Design: a literature search was performed encompassing all Clinical studies assessing the presence of macrophages in dysplastic and non-dysplastic tissues in relation to the prognosis of potentially malignant disorders, without restrictions on year, language, or publication status (in press). Results: Twenty-one articles fully attended the inclusion criteria, which included oral lichen planus (9/21 articles), oral leukoplakia/dysplasia (11/21 articles), oral submucous fibrosis (2/21 articles) and chronic graft-versus-host disease (1/21 articles, n = 12 patients) lesions. Most of the articles indicated that pan macrophages (CD68+) marker and the pro-tumoral M2 macrophage marker (CD163+) were distributed in the connective tissue and subepithelial compartment, with an increase in the number according to the pathological grade (mild, moderated or severe) and area of oral potentially malignant disorders (i.e epithelial or subepithelial layer). Conclusions: This systematic review indicates that there is an increase in the presence of macrophages in oral potentially malignant disorders, and these cells may be involved in the carcinogenesis process.